Basics of enterprise functioning as a single integrated and highly efficient business system - Chupryna, Yu.; Aleksieienko, V.; Matveyev , V.; Polzikov , M. (Ways to Improve Construction Efficiency, 2024)
The article is devoted to the study of the enterprise as a single and effective business system that operates on the basis of the integration of economic, managerial and technological components. In modern conditions of market competition, the efficiency of the enterprise is determined not only by its financial indicators, but also by the ability to adapt to a changing business environment, introduce innovations and optimize internal processes. The main concepts of the systemic approach to enterprise management are considered, in particular integrated business process models that contribute to increasing its efficiency and competitiveness. The principles of strategic enterprise management, the role of digital technologies in its functioning, as well as the importance of integrating stakeholders into the process of making managerial decisions are also analyzed. Particular attention is paid to the issues of balancing the internal resources of the enterprise, increasing its operational efficiency and forming a long-term development strategy. Methods of optimizing financial flows, personnel management, marketing strategies and decision-making processes are studied. Separately, the importance of implementing modern technologies, in particular Big Data analytics, artificial intelligence (AI), automated management systems (ERP) and digital platforms for optimizing business processes is considered. The use of these tools allows not only to increase the productivity of the enterprise, but also to ensure more accurate forecasting of market trends, minimize risks and adapt business models in accordance with the requirements of the time. The article also highlights the role of corporate social responsibility (CSR) in modern business, which contributes not only to increasing customer loyalty, but also to creating sustainable competitive advantages. Given modern challenges, enterprises are faced with the task of effective risk management and developing adaptive strategies that will ensure their stability even in crisis conditions. Thus, the article contains a comprehensive analysis of approaches to managing an enterprise as an integrated business system that ensures sustainable development, flexibility in decision-making and increased efficiency of functioning in a dynamic market environment. The implementation of a strategic approach, innovative technologies and effective resource planning allows enterprises to adapt to modern challenges and ensure their long-term competitiveness.